2011
DOI: 10.4315/0362-028x.jfp-11-126
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Food Safety Perceptions and Practices in a Turkish Community

Abstract: Research has shown that most reported foodborne outbreaks are caused by food prepared and consumed at home, thus emphasizing the importance of consumer food safety knowledge. In this study, 2,000 randomly selected residents from Çanakkale, Turkey, participated in face-to-face interviews to assess their food safety perceptions and practices. Questions covered the attention given to expiration dates, safety certificates, and food additives during shopping; consumption of high-risk foods; safe food handling; sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 19 publications
1
19
2
3
Order By: Relevance
“…This is also coincident with results from Lin et al [15]. Women are significantly more interested in food safety issues than men, although there is no statistically significant relationship between gender and food safety knowledge [35]. This is confirmed in other studies [54,55].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This is also coincident with results from Lin et al [15]. Women are significantly more interested in food safety issues than men, although there is no statistically significant relationship between gender and food safety knowledge [35]. This is confirmed in other studies [54,55].…”
Section: Discussionsupporting
confidence: 88%
“…Younger consumers are less interested in food safety issues than older consumers are [35]. This could explain why the knowledge about Campylobacter in our study differed statistically significant by age group, and young adults < 20 years were the least informed.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…In essence, the information of product's expiration date was used by the consumers to suppress the negative risk of the product, thus avoid direct risks of consuming the products, such as food poisoning, sickness, or even death and any other risks. A study by Zorba and Kaptan (2011) also showed that reading the expiration date in the product's label would give a sense of security for the consumers. A rather surprising result in this study is that the respondents' health condition did not affect their behavior in reading the product's label (p≥0.05).…”
Section: Factors Affecting Consumers' Behavior In Reading the Label Imentioning
confidence: 99%